Problem dyskryminacji kobiet — analiza wybranych teorii neoklasycznych opartych na założeniu o niekonkurencyjnych rynkach pracy - Kuropatwa, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper contains an analysis of neoclassical theories of discrimination, that are based on the assumption of non-competitive labour markets. These theories are presented within the mathematical framework, used in original works of their respective authors. Each theory has been subjected to a brief analysis. The author also assessed factors that could be determined as discriminatory and has examined their actual impact on the phenomenon of discrimination against women on the labour market
Keywords: dyskryminacja kobiet; rynek pracy; neoklasyczne teorie dyskryminacji